A educação física e a construção de imagens de feminilidade no Brasil dos anos 30 e 40 - Silvana Vilodre Goellner (Universidade Federal do Rio Grande do Sul, 2000)
This text is about Physical Education and images of feminility More speoncally, it refers to the corporal and sportive practices, as well as to the visibility of the feminine body in the 30th and 40th of this century. It discloses some political, economical and cultural modifications in the Brazilian society at that period, which had the consequence of making permissible the exhibition of the feminine body, while, at the same time, promoting strategies for its hiding.